PDCD4 Knockdown Induces Senescence in Hepatoma Cells by Up-Regulating the p21 Expression - Guo, Jing; Ozaki, Iwata; Xia, Jinghe; Kuwashiro, Takuya; Kojima, Motoyasu; Takahashi, Hirokazu; Ashida, Kenji; Anzai, Keizo; Matsuhashi, Sachiko (Frontiers in Oncology, 2019)
While the over-expression of tumor suppressor programmed cell death 4 (PDCD4) induces apoptosis, it was recently shown that PDCD4 knockdown also induced apoptosis. In this study, we examined the cell cycle regulators whose activation is affected by PDCD4 knockdown to investigate the contribution of PDCD4 to cell cycle regulation in three types of hepatoma cells: HepG2, Huh7 (mutant p53 and p16-deficient), and Hep3B (p53- and Rb-deficient). PDCD4 knockdown suppressed cell growth in all three cell lines by inhibiting Rb phosphorylation via down-regulating the expression of Rb itself and CDKs, which phosphorylate Rb, and up-regulating the expression of the CDK inhibitor p21 through a p53-independent pathway. We also found that apoptosis was induced in a p53-dependent manner in PDCD4 knockdown HepG2 cells (p53+), although the mechanism of cell death in PDCD4 knockdown Hep3B cells (p53-) was different. Furthermore, PDCD4 knockdown induced cellular senescence characterized by β-galactosidase staining, and p21 knockdown rescued the senescence and cell death as well as the inhibition of Rb phosphorylation induced by PDCD4 knockdown. Thus, PDCD4 is an important cell cycle regulator of hepatoma cells and may be a promising therapeutic target for the treatment of hepatocellular carcinoma.